Intuitive to Strategic Translanguaging: Insights From Vietnamese EFL Classrooms - Ngo Cong-Lem (Profile Issues in Teachers' Professional Development)
This article reports a qualitative case study on the translanguaging practices of Vietnamese English-as-a-foreign-language (EFL) educators and explores the mechanisms behind individual differences in their practices through an integrative cultural-historical activity theory perspective. Data were collected through semi-structured interviews, classroom observations, and post-observation interviews with three educators at a public university in Vietnam. The findings highlight diverse functions of translanguaging, including checking comprehension, emphasizing content, and reducing English-speaking anxiety. Rooted in Vygotsky’s Zone of Proximal Development (ZPD), this research introduces Proximal Language Scaffolding to highlight a strategic approach to using L1 and L2 for language learning within students’ ZPD. This research provides new insights into the nuanced implementation of translanguaging in EFL contexts and offers significant implications for teacher development and educational practices.